Interstitial nephritis. - Dhillon, S. (BMJ Group, 1997)
Interstitial nephritis is an inflammatory process within the renal interstitium, and was one of the first observations made in the description of renal histopathology. Many different conditions are associated with an interstitial nephritis, and as a clinical diagnosis the term has little use unless causation is defined. However, there has been recent interest in the possibility of a common mechanism causing irreversible renal damage and eventually renal failure in many different types of interstitial nephritis. Such damage could take place due to blood-borne inflammatory mediators, or could be due to renal tubular inflammation related to abnormal components of the glomerular filtrate in renal failure, such as proteins or lipids. If such research were to result in effective therapy for interstitial nephritis, the progression of many forms of renal disease to end stage renal failure could be ameliorated.